Icephobicity studies of superhydrophobic coating on aluminium. (3rd October 2021) - Tan, Xinyu; Wang, Man; Tu, Yiteng; Xiao, Ting; Alzuabi, Sarah; Xiang, Peng; Guo, Runhua; Chen, Xiaobo
ABSTRACT: Mechanically robust superhydrophobic (SHP) and icephobic performances are highly needed for an anti-icing surface in practical applications. Here, a SHP coating is prepared on the aluminium (Al) substrate using hydrothermal reaction and subsequent modification of hexadecyltrimethoxysilane, showing a water contact angle larger than 158° and a sliding angle (SA) less than 5°. This SHP coating displays a robust hydrophobic performance in acidic or alkaline solutions, after sand abrasion and consecutive icing/deicing cycles. It largely reduces ice adhesive strength and delays starting icing time on Al. Therefore, this work may shine some light in engineering aluminium-based materials to avoid ice accumulation.